The prevalence of burnout and sources of stress among doctoral students in Universiti Sains Malaysia - Ismail, Nur Nadia (2021)
INTRODUCTION Doctor of Philosophy is the highest degree in academic undertaking one could have achieved. Mostly, the motivaion to persue the education is due to self-satisfaction, interest in contributing back to the community, societal approval and better career opportunity. However, recent studies had proposed a higher prevalence of developing mental health symptoms suffered by students during their doctoral studies compared to age match general population. The prolonged stress in a student’s life often associated with burnout periods whereby it rises negative outcomes at several various social, personal, academic and career levels. Therefore, finding the root cause of this stress and its association to the socio-demographic backgrounds are pertinent to assist the relevant stakeholders in preventing burnouts among doctoral students. Thus, authors investigated the prevalence of burnout and identify the sources of stress among doctoral student in Universiti Sains Malaysia.